Engineering Nicotiana benthamiana for production of active cannabinoid synthases via secretory pathway optimization - Omayra C. Bolaños-Martínez; Anna Urbanetz; Daniel Maresch; Richard Strasser; Sornkanok Vimolmangkang (Biotechnology Reports)
The production of cannabinoid compounds such as Δ9-tetrahydrocannabinol (THC), cannabidiol (CBD) and cannabichromene (CBC) with potential pharmaceutical applications is growing sharply. However, challenges such as the low yield of minor cannabinoids, legal restrictions on cultivation, and the complexity and cost of purification from the Cannabis sativa plant necessitate a biotechnological approach. Since the biosynthetic pathway is disclosed, cannabinoids have been produced in yeast, insect cells and plants mainly by the heterologous expression of tetrahydrocannabinol acid synthase (THCAS). THCAS and cannabidiolic acid synthase (CBDAS) use cannabigerolic acid (CBGA) as a substrate. In this study, we transiently expressed recombinant forms of THCAS and CBDAS in leaves of Nicotiana benthamiana. Our results demonstrate that efficient expression in the secretory pathway relies on replacing the endogenous signal peptide with a heterologous one. Both proteins were successfully secreted to the apoplast. MS-based analysis of the purified proteins revealed that they are heavily glycosylated with mainly Golgi-processed complex type N-glycans. In planta enzymatic removal of N-glycans indicated that glycosylation plays a role for CBDAS protein folding or stability. Finally, in vitro assays with CBGA showed that the plant-made recombinant CBDAS and THCAS are enzymatically active.